Composite diaphragm, preparation method thereof and secondary battery comprising composite diaphragm

By using the modified polypropylene fibrous membrane on the septum of the secondary battery, the problem of dissolving metal ions through the diaphragm deposition of the diaphragm was solved, and the battery performance improvement and the simplification of the preparation process were achieved.

CN119381696APending Publication Date: 2025-01-28BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310920402.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively suppress the metal ions dissolved in the positive electrode material during the long-term cycle of the secondary battery and deposited on the negative electrode through the separator, resulting in attenuation of the battery capacity.

Method used

The composite diaphragm is composed of a modified polyacrylpine fibrous membrane and the diaphragm base membrane. The modified polypropylene fibrous membrane is modified through the polyamine branches. It has a good metal ion chelating effect to avoid metal ion deposition.

Benefits of technology

Effectively suppress the metal ions in the positive material through the diaphragm and deposit in the negative electrode, improve the cycle life and performance of the battery, and the preparation process is simple, and there is no additional additive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004358562740000031
    Figure BDA0004358562740000031
Patent Text Reader

Abstract

The invention provides a composite diaphragm, a preparation method thereof and a secondary battery comprising the composite diaphragm. The composite diaphragm comprises a diaphragm base membrane and a modified polyacrylonitrile fiber membrane compounded on the surface of the diaphragm base membrane, the modified polyacrylonitrile fiber membrane comprises modified polyacrylonitrile fibers, and the modified polyacrylonitrile is polyacrylonitrile grafted with polyamine. The composite diaphragm is prepared by the following steps: preparing polyacrylonitrile fibers through electrostatic spinning, reacting the polyacrylonitrile fibers with polyamine, and coating a diaphragm base membrane with the modified polyacrylonitrile fibers. The composite diaphragm provided by the invention has good chelation and adsorption effects on metal ions, and can inhibit capacity fading caused by the fact that the metal ions dissolved in a positive electrode material in a long-term circulation process penetrate through the diaphragm and are deposited on a negative electrode, so that the battery performance is improved; and the diaphragm base membrane and the chelating group are integrally formed, so that no additional additive is needed when the modified polyacrylonitrile fiber membrane is formed, and the preparation process is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a composite diaphragm, a preparation method thereof and a secondary battery comprising the composite diaphragm. Background Art

[0002] Transition metal elements in batteries have a significant effect on improving battery performance. For example, in the nickel-cobalt-manganese-oxide lithium positive electrode material, the transition metal elements Ni, Co, and Mn have different effects on the material performance. Among them, the higher the content of Ni, the higher the specific capacity of the material can be provided. However, when Ni is in the charging state, 4+ It is extremely unstable and can easily cause material safety issues; increasing the content of Co can reduce the degree of cation mixing in the material, but will significantly increase the cost of the material; increasing the content of Mn can stabilize the structure of the material, but will significantly reduce the discharge capacity of the material. Therefore, the performance of lithium nickel cobalt manganese oxide with different Ni, Co, and Mn ratios is also different.

[0003] Through the analysis of failed batteries, it was found that transition metal elements existed in the negative electrode of the battery, which indicates that the dissolution of transition metal ions is a characteristic of battery failure. Studies have shown that hydrofluoric acid, a byproduct of the electrochemical reaction inside the battery, will react with the transition metal ions on the surface of the positive electrode, which will cause the loss of transition metal elements on the one hand, and on the other hand, the generated byproducts will have a negative impact on battery performance; in particular, the dissolved transition metal ions will be deposited on the negative electrode, which will cause the battery capacity to decay.

[0004] Ion conduction must rely on the porous structure of the separator, and the porous structure of the separator will also cause transition metal ions to cross to the negative electrode and produce deposition. Kevin Leung (see "First Principles Modeling of Mn(II)Migration above and Dissolution from Li x Mn2O4(001)Surfaces", "chemistry of materials" confirmed that Li x The dissolution process of Mn in Mn2O4 may be as follows: (a) EC molecular fragments are adsorbed on the (001) surface of LMO, promoting the dissolution of Mn; (b) Mn migrates to the amorphous sites on the surface of LMO; c) Mn(Ⅱ) dissolves; d) Mn(Ⅱ) is embedded in the negative electrode SEI film, catalyzing the decomposition of the organic components of the SEI film and producing CO2.

[0005] In order to solve the problem of metal ion deposition, in the prior art, a functional coating with metal ion adsorption capacity is usually prepared on the surface of the diaphragm, and the coating is applied on the surface of the diaphragm, so that the chelating agent in the coating reacts with the metal ions to achieve the effect of adsorbing the metal ions. However, this method has a complicated preparation process and most of them require additional additives.

[0006] Therefore, how to prepare a functional film with metal ion adsorption capacity and composite it with the diaphragm base film to reduce the deposition of metal ions at the negative electrode is of great significance for improving the long-cycle performance of the battery. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a composite diaphragm, a preparation method thereof and a secondary battery containing the same. The modified polyacrylonitrile fiber membrane in the composite diaphragm has good chelation and adsorption effects on metal ions, which can inhibit the metal ions dissolved in the positive electrode material from passing through the diaphragm and depositing on the negative electrode during long-term circulation, resulting in capacity decay. The diaphragm base membrane and the modified polyacrylonitrile fiber membrane are integrally formed, and no additional additives are required when forming the modified polyacrylonitrile fiber membrane, and the preparation process is simple.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a composite diaphragm, comprising a diaphragm base membrane, and a modified polyacrylonitrile fiber membrane composited on the surface of the diaphragm base membrane;

[0010] The modified polyacrylonitrile fiber membrane comprises modified polyacrylonitrile fiber, and the modified polyacrylonitrile is polyacrylonitrile grafted with polyamine.

[0011] It should be noted that the polyamine in the present invention contains at least one amino group to react with polyacrylonitrile.

[0012] In the composite diaphragm provided by the present invention, the fiber membrane formed by polyacrylonitrile grafted with polyamine contains a large amount of amino groups, which has a good chelating effect on metal ions. The composite diaphragm is used in a secondary battery to prevent the metal ions dissolved from the positive electrode material during long-term circulation from passing through the diaphragm and depositing on the negative electrode, thereby improving the battery performance.

[0013] In addition, polyacrylonitrile has both thickening and bonding properties and can be used as a battery binder. The present invention uses fibrous polyacrylonitrile to form a fiber membrane on the surface of the diaphragm base membrane, which not only improves the membrane strength on the surface of the diaphragm base membrane, but also makes the preparation process more complete. At the same time, when forming the fiber membrane, no additional thickener or other additives are required, which simplifies the process; in addition, the cyanide group in polyacrylonitrile reacts with the amino group in the polyamine, and the related reactants can stably exist in the electrochemical system of the battery, and will not affect the battery performance, thereby avoiding the complex synthesis reaction of polyacrylonitrile and the metal chelating agent and the impact on the overall battery system.

[0014] The present invention has no special limitation on the diaphragm base film, which can be a conventional diaphragm in the art, such as a polyethylene (PE) diaphragm, a polypropylene (PP) diaphragm, a polyethylene / polypropylene (PE / PP) diaphragm, a polyethylene / polypropylene / polyethylene (PE / PP / PE) diaphragm, a polypropylene / polyethylene / polypropylene (PP / PE / PP) diaphragm, and the like.

[0015] The thickness of the separator base film may be 1-50 μm.

[0016] In some embodiments of the present invention, the thickness of the modified polyacrylonitrile fiber membrane is 1-8μm; for example, it can be 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm or 8μm, etc.

[0017] In some embodiments of the present invention, the porosity of the modified polyacrylonitrile fiber membrane is 20-80%, for example, it can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, etc.

[0018] In some embodiments of the present invention, the diameter of the modified polyacrylonitrile fiber is 100-500 nm; for example, it can be 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm.

[0019] In some embodiments of the present invention, the grafting rate of the modified polyacrylonitrile is 10-100%; for example, it can be 10%, 20%, 30%, 40%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 99%, etc.

[0020] In the present invention, the grafting rate of the modified polyacrylonitrile refers to the ratio of the number of acrylonitrile units reacted with polyamine to the total amount of acrylonitrile units.

[0021] In some embodiments of the present invention, the weight average molecular weight of the polyacrylonitrile is 120,000-150,000.

[0022] In some embodiments of the present invention, the polyamine is selected from polyene polyamines, for example, one or more selected from diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine and hexaethyleneheptamine.

[0023] In some embodiments of the present invention, the molecular structure of the polyamine contains two or more amine groups, and does not contain tertiary amine groups and secondary amine groups. For example, the polyamine is selected from one or more of ethylenediamine, propylenediamine, butylenediamine and pentamethylenediamine.

[0024] As a preferred embodiment, the modified polyacrylonitrile fiber membrane does not contain a thickener.

[0025] It can be understood that the modified polyacrylonitrile fiber membrane does not contain a thickener only means that no thickener is added during the film formation process of the modified polyacrylonitrile fiber membrane. The thickener with an error level content introduced during the preparation process due to other reasons should be regarded as within the scope of protection of this application.

[0026] In some embodiments of the present invention, the composite diaphragm further comprises a ceramic layer disposed on a side of the diaphragm base film away from the modified polyacrylonitrile fiber membrane. By disposing the ceramic layer on the diaphragm, it is helpful to improve the puncture resistance of the diaphragm, enhance the safety of the battery, and improve the liquid retention capacity.

[0027] The present invention has no special restrictions on the type of ceramic layer. The ceramic layer can be an electrochemically inert metal or non-metal oxide, such as Al2O3, TiO2, SiO2, etc.; it can also be a solid electrolyte layer, such as an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a hydride solid electrolyte, a nitride solid electrolyte, a boride solid electrolyte, etc.; the above-mentioned solid electrolyte materials are all well-known in the art and will not be described in detail here.

[0028] In a second aspect, the present invention provides a method for preparing the composite diaphragm according to the first aspect, the preparation method comprising the following steps:

[0029] (1) dissolving polyacrylonitrile in an organic solvent and obtaining polyacrylonitrile fibers by electrospinning;

[0030] (2) reacting the polyacrylonitrile fiber with polyamine in an alkaline aqueous solution to obtain modified polyacrylonitrile fiber;

[0031] (3) The modified polyacrylonitrile fiber is dissolved in an organic solvent and coated on one side of a diaphragm base film, and a ceramic layer is coated or not coated on the other side of the diaphragm base film, and the composite diaphragm is obtained after drying.

[0032] In the present invention, taking triethylenetetramine as an example, the reaction formula of triethylenetetramine with polyacrylonitrile is as follows:

[0033]

[0034] In some embodiments of the present invention, the organic solvents in step (1) and step (3) are independently selected from one or more of dimethylacetamide (DMAC), N,N-dimethylamide, acetone, ethanol and ethylene glycol monomethyl ether.

[0035] In some embodiments of the present invention, the concentration of the electrospinning solution in step (1) is 0.8-1.3 g / L; for example, it can be 0.8 g / L, 0.9 g / L, 1 g / L, 1.1 g / L, 1.2 g / L or 1.3 g / L, etc.

[0036] In some embodiments of the present invention, the conditions for electrospinning include: an electric field strength of 0.5-1.5 kV / cm, for example, 0.5 kV / cm, 0.6 kV / cm, 0.8 kV / cm, 1 kV / cm, 1.2 kV / cm, 1.3 kV / cm or 1.5 kV / cm, etc.; an electrospinning solution flow rate of 0.5-1.5 mL / h, for example, 0.5 mL / h, 0.6 mL / h, 0.8 mL / h, 1 mL / h, 1.2 mL / h, 1.3 mL / h or 1.5 mL / h, etc.

[0037] In some embodiments of the present invention, the alkaline aqueous solution in step (2) is a 10-60 g / L (10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 55 g / L or 60 g / L, etc.) aqueous solution of sodium carbonate.

[0038] In some embodiments of the present invention, the reaction temperature in step (2) is 110-140°C, for example, it can be 110°C, 112°C, 115°C, 118°C, 120°C, 122°C, 125°C, 128°C, 130°C, 132°C, 135°C, 138°C or 140°C, etc.; the reaction time is 4-7h, for example, it can be 4h, 4.5h, 5h, 5.5h, 6h, 6.5h or 7h, etc.

[0039] In some preferred embodiments of the present invention, the preparation method comprises the following steps:

[0040] (1) Preparation of polyacrylonitrile fiber:

[0041] Add polyacrylonitrile to an organic solvent, stir magnetically at a temperature of 30-60°C until the solution becomes clear and transparent, then transfer the solution to an ultrasonic device at a constant temperature of 30-60°C, ultrasonicate for 1-3 hours, and obtain a uniform polyacrylonitrile electrospinning solution with a concentration of 0.8-1.3 g / L; electrospin the polyacrylonitrile electrospinning solution under conditions of an electric field strength of 1 kV / cm and a flow rate of 1 mL / h, and obtain polyacrylonitrile fibers after drying;

[0042] (2) Preparation of modified polyacrylonitrile fiber:

[0043] Prepare a sodium carbonate aqueous solution with a concentration of 10-60g / L, add polyamine, mix and add to polyacrylonitrile fiber, heat to 110-140°C, react for 4-7h until the polyacrylonitrile fiber turns yellow; then wash with deionized water several times, dry in a vacuum oven at 30-60°C for 20-30h to obtain modified polyacrylonitrile fiber;

[0044] (3) Preparation of composite diaphragm:

[0045] The modified polyacrylonitrile fiber is dissolved in an organic solvent and coated on one side of a diaphragm base film, and a ceramic layer is coated or not coated on the other side of the diaphragm base film, and the composite diaphragm is obtained after drying.

[0046] In the present invention, since polyacrylonitrile has both thickening and bonding effects, combined with electrospinning technology, the fiber membrane formed can reach the micron level, and the fiber membrane contains a large number of voids. While adsorbing metal ions, it can better composite with the diaphragm base membrane, will not affect the wetting ability of the electrolyte, and can improve the overall performance and compatibility of the diaphragm.

[0047] In a third aspect, the present invention provides a secondary battery, the secondary battery comprising the composite separator according to the first aspect;

[0048] The modified polyacrylonitrile fiber membrane in the composite separator is arranged to face the positive electrode.

[0049] Preferably, the molecular structure of the positive electrode active material of the secondary battery positive electrode contains transition metal elements.

[0050] It is understandable that the present application has no special requirements for the type of positive electrode active material. Without violating the inventive concept of the present application, any known type of positive electrode active material can be used in the present application. As an illustrative example only, not a limitation on the scope of protection, the positive electrode active material can be a layered oxide positive electrode active material, a spinel positive electrode active material, an olivine positive electrode active material, etc. The layered oxide positive electrode active material (for example, a rock salt layered oxide) contains one or more lithium-based positive electrode active materials selected from the following: LiCoO2 (LCO), LiNi xMn y Co 1-x-y O2 (where 0≤x≤1 and 0≤y≤1), LiNi 1-x-y Co x Al y O2 (where 0≤x≤1 and 0≤y≤1), LiNi x Mn 1-x O2 (where 0≤x≤1), and Li 1+x MO2 (wherein M is one of Mn, Ni, Co and Al and 0≤x≤1). The spinel positive electrode comprises one or more lithium-based positive electrode electroactive materials selected from the following: LiMn2O4 (LMO) and LiNi 0.5 Mn 1.5 O4. The olivine-type positive electrode active material comprises one or more lithium-based positive electrode electroactive materials LiMPO4 (wherein M is at least one of Fe, Ni, Co and Mn).

[0051] It is understandable that positive electrode materials containing transition metal ions such as Mn are particularly suitable for the present application, because the composite diaphragm structure of the present application can effectively prevent the deposition of metal ions at the negative electrode, improve battery performance, and enable the positive electrode active material to perform better.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] In the composite diaphragm provided by the present invention, the fiber membrane formed by polyacrylonitrile modified by polyamine grafting contains a large amount of amino groups, which has a good chelating effect on metal ions. The composite diaphragm is used in a secondary battery to prevent the metal ions dissolved in the positive electrode material from passing through the diaphragm and depositing on the negative electrode during long-term circulation, thereby improving the battery performance. Among them, polyacrylonitrile has both thickening and bonding properties, and no additional thickener or other additives are required when forming the fiber membrane. The diaphragm base membrane and the modified polyacrylonitrile fiber membrane are integrally formed, and the preparation process is simple. DETAILED DESCRIPTION

[0054] The technical solution of the present invention is further described below by means of specific implementation methods. It should be understood by those skilled in the art that the specific implementation methods are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0055] Example 1

[0056] This embodiment provides a composite diaphragm, and the preparation method thereof is as follows:

[0057] (1) Preparation of polyacrylonitrile fiber:

[0058] 100 g of polyacrylonitrile (from Aladdin, Mw=150,000) powder was weighed and added to 1000 mL of DMAC. The solution was magnetically stirred at 45°C until the solution became clear and transparent. The solution was then transferred to an ultrasonic device at a constant temperature of 45°C and ultrasonicated for 2 hours to obtain a uniform polyacrylonitrile electrospinning solution. The polyacrylonitrile electrospinning solution was electrospun under the conditions of an electric field strength of 1 kV / cm and a flow rate of 1 mL / h, and polyacrylonitrile fibers were obtained after drying.

[0059] (2) Preparation of modified polyacrylonitrile fiber:

[0060] Dissolve 40 g of Na2CO3 in 2 L of deionized water, then add 120 mL of triethylenetetramine, mix and add to the polyacrylonitrile fiber obtained in step (1), heat to 125°C, react for 5 hours, and the polyacrylonitrile fiber turns yellow; then wash with deionized water several times, dry in a vacuum oven at 60°C for 20 hours, and obtain modified polyacrylonitrile fiber with an average diameter of 300 nm.

[0061] (3) Preparation of composite diaphragm:

[0062] The modified polyacrylonitrile fiber obtained in step (2) is dissolved in DMAC to prepare a solution with a solid content of 50%, which is coated on one side of the PE diaphragm and dried to obtain the composite diaphragm, wherein the modified polyacrylonitrile fiber membrane has a thickness of 3 μm and a porosity of 30%.

[0063] Example 2

[0064] This embodiment provides a composite diaphragm, and the preparation method thereof is as follows:

[0065] (1) Preparation of polyacrylonitrile fiber:

[0066] 100 g of polyacrylonitrile (from Aladdin, Mw=150,000) powder was weighed and added to 800 mL of DMAC. The solution was magnetically stirred at 45°C until the solution became clear and transparent. The solution was then transferred to an ultrasonic device at a constant temperature of 45°C and ultrasonicated for 2 hours to obtain a uniform polyacrylonitrile electrospinning solution. The polyacrylonitrile electrospinning solution was electrospun under the conditions of an electric field strength of 1 kV / cm and a flow rate of 1 mL / h, and polyacrylonitrile fibers were obtained after drying.

[0067] (2) Preparation of modified polyacrylonitrile fiber:

[0068] Dissolve 60 g of Na2CO3 in 1 L of deionized water, then add 160 mL of ethylenediamine, mix and add to the polyacrylonitrile fiber obtained in step (1), heat to 110°C, react for 7 hours, and the polyacrylonitrile fiber turns yellow; then wash with deionized water several times, dry in a vacuum oven at 60°C for 20 hours, and obtain modified polyacrylonitrile fiber with an average diameter of 300 nm.

[0069] (3) Preparation of composite diaphragm:

[0070] The modified polyacrylonitrile fiber obtained in step (2) is dissolved in DMAC to prepare a solution with a solid content of 40%, which is coated on one side of the PP diaphragm and dried to obtain the composite diaphragm, wherein the thickness of the modified polyacrylonitrile fiber membrane is 3 μm.

[0071] Example 3

[0072] This embodiment provides a composite diaphragm, and the preparation method thereof is as follows:

[0073] (1) Preparation of polyacrylonitrile fiber:

[0074] 100 g of polyacrylonitrile (from Aladdin, Mw=150000) powder was weighed and added to 1200 mL of N,N-dimethylamide. The solution was magnetically stirred at 45°C until the solution became clear and transparent. The solution was then transferred to an ultrasonic device at a constant temperature of 45°C and ultrasonicated for 2 hours to obtain a uniform polyacrylonitrile electrospinning solution. The polyacrylonitrile electrospinning solution was electrospun under the conditions of an electric field strength of 1 kV / cm and a flow rate of 1 mL / h, and polyacrylonitrile fibers were obtained after drying.

[0075] (2) Preparation of modified polyacrylonitrile fiber:

[0076] Dissolve 30 g of Na2CO3 in 3 L of deionized water, then add 90 mL of diethylenetriamine, mix and add to the polyacrylonitrile fiber obtained in step (1), heat to 140°C, react for 4 hours, and the polyacrylonitrile fiber turns yellow; then wash with deionized water several times, dry in a vacuum oven at 60°C for 20 hours, and obtain modified polyacrylonitrile fiber with an average diameter of 300 nm.

[0077] (3) Preparation of composite diaphragm:

[0078] The modified polyacrylonitrile fiber obtained in step (2) is dissolved in DMAC to prepare a solution with a solid content of 50%, which is coated on one side of the PP diaphragm and dried to obtain the composite diaphragm, wherein the thickness of the modified polyacrylonitrile fiber membrane is 3 μm.

[0079] Example 4

[0080] This embodiment provides a composite diaphragm, and the preparation method thereof is as follows:

[0081] (1) Preparation of polyacrylonitrile fiber:

[0082] 100 g of polyacrylonitrile (from Aladdin, Mw=150,000) powder was weighed and added to 1000 mL of DMAC. The solution was magnetically stirred at 45°C until the solution became clear and transparent. The solution was then transferred to an ultrasonic device at a constant temperature of 45°C and ultrasonicated for 2 hours to obtain a uniform polyacrylonitrile electrospinning solution. The polyacrylonitrile electrospinning solution was electrospun under the conditions of an electric field strength of 1 kV / cm and a flow rate of 1 mL / h, and polyacrylonitrile fibers were obtained after drying.

[0083] (2) Preparation of modified polyacrylonitrile fiber:

[0084] Dissolve 50 g of Na2CO3 in 2.5 L of deionized water, then add 140 mL of tetraethylenepentamine, mix and add to the polyacrylonitrile fiber obtained in step (1), heat to 130°C, react for 6 hours, and the polyacrylonitrile fiber turns yellow; then wash with deionized water several times, dry in a vacuum oven at 60°C for 20 hours, and obtain modified polyacrylonitrile fiber with an average diameter of 300 nm.

[0085] (3) Preparation of composite diaphragm:

[0086] The modified polyacrylonitrile fiber obtained in step (2) is dissolved in DMAC to prepare a solution with a solid content of 35%, which is coated on one side of the PP diaphragm and dried to obtain the composite diaphragm, wherein the thickness of the modified polyacrylonitrile fiber membrane is 3 μm.

[0087] Comparative Example 1

[0088] This comparative example provides a composite diaphragm, which is different from Example 1 only in that step (2) is not performed, and in step (3), the polyacrylonitrile fiber obtained in step (1) is used for coating.

[0089] Preparation of lithium-ion batteries:

[0090] Positive electrode sheet: NCM811, PVDF and super-P were mixed in a solvent N-methylpyrrolidone at a mass ratio of 95:3:2, and stirred evenly to obtain a positive electrode slurry; the positive electrode slurry was coated on the surface of aluminum foil (the thickness of the coating after cold pressing was 140 μm), baked at 120°C for 1 hour, and cold pressed, cut and slit to obtain a positive electrode sheet;

[0091] Negative electrode sheet: Graphite, PAA and super-P were mixed in deionized water at a mass ratio of 95:3:2, and stirred evenly to obtain a negative electrode slurry; the negative electrode slurry was coated on the surface of the copper foil (the thickness of the coating after cold pressing was 85 μm), baked at 120°C for 1 hour, and cold pressed, cut and slit to obtain a negative electrode sheet;

[0092] Electrolyte: LiPF6 ethylene carbonate solution, concentration 1 mol / L;

[0093] Diaphragm: The composite diaphragms provided in the above embodiments and comparative examples were used respectively, and a PE diaphragm was used as a comparison;

[0094] The positive electrode sheet, the separator and the negative electrode sheet are stacked and packaged in order to prepare a lithium-ion battery.

[0095] Cycle performance test: At a temperature of 25℃±2℃, in the first step, charge with a current of 1C to the final voltage (4.25V), the cut-off current is 0.05C, and stand for 30 minutes; in the second step, discharge with 1C to the final discharge voltage (2.75V), record the initial discharge capacity, and stand for 30 minutes; cycle the first and second steps, and the number of cycles when the cycle capacity drops to 80% of the initial discharge capacity is taken as the cycle life.

[0096] After the cycle test, the battery was disassembled and the content of Ni, Co, and Mn elements in the negative electrode was tested using an inductively coupled plasma (ICP) spectrometer.

[0097] The results of the above tests are shown in Table 1 below:

[0098] Table 1

[0099] Diaphragm Cycle life (cycles) Ni content (wt%) Co content (wt%) Mn content (wt%) Example 1 3000 0.0005 0 0.007 Example 2 3041 0.0003 0.0003 0.002 Example 3 3084 0.0001 0.0001 0 Example 4 2986 0.0012 0.0011 0.003 Comparative Example 1 2406 0.0195 0.0032 0.0099 PE diaphragm 2120 0.0211 0.0051 0.0121

[0100] It can be seen from the test results in Table 1 that, compared with Comparative Example 1 and the common PE separator, the composite separator provided by the present invention significantly reduces the deposition of transition metal elements on the negative electrode and improves the cycle life of the battery.

[0101] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A composite diaphragm, characterized in that: It includes a diaphragm base film, and a modified polyacrylonitrile fiber film composited on the surface of the diaphragm base film; The modified polyacrylonitrile fiber membrane comprises modified polyacrylonitrile fiber, and the modified polyacrylonitrile is polyacrylonitrile grafted with polyamine.

2. The composite diaphragm according to claim 1, characterized in that: The modified polyacrylonitrile fiber membrane has a thickness of 1-8 μm; Preferably, the porosity of the modified polyacrylonitrile fiber membrane is 20-80%.

3. The composite diaphragm according to claim 1 or 2, characterized in that: The diameter of the modified polyacrylonitrile fiber is 100-500nm.

4. The composite diaphragm according to any one of claims 1 to 3, characterized in that: The grafting rate of the modified polyacrylonitrile is 10-100%; Preferably, the weight average molecular weight of the polyacrylonitrile is 120,000-150,000.

5. The composite diaphragm according to any one of claims 1 to 4, characterized in that: The polyamine is selected from one or more of ethylenediamine, propylenediamine, butylenediamine, pentylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine and hexaethyleneheptamine.

6. The composite diaphragm according to any one of claims 1 to 5, characterized in that: The composite diaphragm further comprises a ceramic layer arranged on a side of the diaphragm base membrane away from the modified polyacrylonitrile fiber membrane.

7. A method for preparing a composite diaphragm according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) dissolving polyacrylonitrile in an organic solvent as an electrospinning solution, and obtaining polyacrylonitrile fibers by electrospinning; (2) reacting the polyacrylonitrile fiber with polyamine in an alkaline aqueous solution to obtain modified polyacrylonitrile fiber; (3) The modified polyacrylonitrile fiber is dissolved in an organic solvent and coated on one side of a diaphragm base film, and a ceramic layer is coated or not coated on the other side of the diaphragm base film, and the composite diaphragm is obtained after drying.

8. The preparation method according to claim 7, characterized in that: The organic solvents in step (1) and step (3) are each independently selected from one or more of dimethylacetamide, N,N-dimethylamide, acetone, ethanol and ethylene glycol monomethyl ether; Preferably, the concentration of the electrospinning solution in step (1) is 0.8-1.3 g / L; Preferably, the electrospinning conditions include: an electric field strength of 0.5-1.5 kV / cm, and an electrospinning solution flow rate of 0.5-1.5 mL / h.

9. The preparation method according to claim 7 or 8, characterized in that: The alkaline aqueous solution in step (2) is a 10-60 g / L sodium carbonate aqueous solution; Preferably, the reaction temperature in step (2) is 110-140° C. and the reaction time is 4-7 h.

10. A secondary battery, characterized in that: A composite diaphragm comprising any one of claims 1 to 6; The modified polyacrylonitrile fiber membrane in the composite separator is arranged to face the positive electrode.

Citation Information

Patent Citations

  • A composite nanofiber lithium-ion battery separator and its preparation method

    CN102299287A

  • Lithium ion battery

    CN107528086A

  • Preparation method and using method for polyamino / amidoxim-modified multifunctional ion exchange fibers

    CN109289803A

  • Diaphragm capable of capturing transition metal ions, and preparation method and application thereof

    CN113224460A

  • Method for making combination of electrode and membrane for secondary battery

    KR101411285B1